Congenital hypoplasia of depressor anguli oris muscle: A genetically determined condition?. Issue 12 (December 1974) - Papadatos, C.; Alexiou, D.; Nicolopoulos, D.; Mikropoulos, H.; Hadzigeorgiou, E.
Abstract : The frequency of hypoplasia of the depressor anguli oris muscle was 37 cases among 4 530 consecutive births (8·2%). Diagnosis was based on clinical and electromyographic studies. Severe congenital anomalies were detected in 3 of the 37 cases, while another 3 newborns had minor congenital defects. In 17 of the 37 cases there were first- or second-degree relatives with lower lip asymmetry. A minimum of 13 out of the 74 parents of the probands were affected. The high incidence of affection among first-degree relatives of the probands is strong evidence of hereditary factors playing a role in the aetiology of this anomaly.